Presentation Dossier Stories of the São Francisco River: Subjects, Territories, and Temporalities - Santana, Pedro Abelardo; Vieira da Cruz, José (Revista Crítica Histórica, 2023)
Presentation Dossier Stories of the São Francisco River: Subjects, Territories, and Temporalities